"Love hurts": romantic attachment and depressive symptoms in pregnant adolescent and young adult couples. - Desrosiers, Alethea; Sipsma, Heather; Callands, Tamora; Hansen, Nathan; Divney, Anna; Magriples, Urania; Kershaw, Trace (Journal of clinical psychology, 2014)
The current study investigates the relationship between romantic attachment style and depressive symptoms between both members of pregnant adolescent and young adult couples.
Keywords: Adolescent; Adult; Depression; Female; Humans; Interpersonal Relations; Love; Male; Object Attachment; Pregnancy; Sexual Partners; Young Adult